1989
DOI: 10.1203/00006450-198902000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Euglycemic Hyperinsulinemia on Neonatal Canine Hepatic and Muscle Metabolism

Abstract: ABSTRACT. The effects of euglycemic hyperinsulinemia on hepatic and muscle metabolism were determined in the fasted newborn dog during the first day of life. Hyperinsulinemia was sustained with a primed constant infusion of insulin whereas euglycemia was maintained with an intravenous infusion of 10% glucose using the insulin clamp technique. Euglycemic hyperinsulinemia caused an increase of glucose utilization from 43.9 f 3.7 to 66.5 + 5.4 ~mol/kg/min ( p < 0.001) and reduced endogenous glucose production to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Clamp experiments have shown incomplete suppression of glucose production in puppies despite very high insulin levels, whereas total suppression was found in adult dogs at corresponding insulin levels (6,7). These results indicate the presence of insulin resistance in the puppies (6,7). Corresponding observations were made by Cowett et al (8) in comparisons of lambs and ewes.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Clamp experiments have shown incomplete suppression of glucose production in puppies despite very high insulin levels, whereas total suppression was found in adult dogs at corresponding insulin levels (6,7). These results indicate the presence of insulin resistance in the puppies (6,7). Corresponding observations were made by Cowett et al (8) in comparisons of lambs and ewes.…”
Section: Discussionsupporting
confidence: 75%
“…It has been discussed whether the defective glucose regulation in newborn infants and animals is due to lack of a hepatic response to an increased plasma glucose concentration, low insulin secretion, or hepatic or peripheral insulin resistance. Clamp experiments have shown incomplete suppression of glucose production in puppies despite very high insulin levels, whereas total suppression was found in adult dogs at corresponding insulin levels (6,7). These results indicate the presence of insulin resistance in the puppies (6,7).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Insulin resistance has been previously investigated in our laboratory using the euglycemic hyperinsulinemic clamp technique in newborn and adult dogs. Newborn dogs did not consistently suppress endogenous glucose production and never achieved maximal glucose metabolization in the presence of hyperinsulinemia when compared with adult dogs (9). These studies indicated that insulin resistance in the newborn dog occurred in the liver (continued glucose production) and skeletal muscle (reduced glucose metabolization).…”
Section: Boundmentioning
confidence: 85%